Role Of Internal Audit In The Public Sector In Kurdstan Recion Of Iraq - Hamawandy, Nawzad Majeed; Omer, Abdul Jalil; Salih, Houshyar Abdulrahman; Ali, Ranjdar Mustafa `; Abubakr, Zaito Awla; Jamil, Diyar Abdulmajeed; Heayyiz, Dana DLawar (The journal of contemporary issues in business and government, 2021)
The main purpose of this study is to investigate the role of internal audit in the Kurdistan public sector. This investigation is focused on ministries and organisations in Arbil, the capital and largest city of Kurdistan, as these are representative of all other sectors. The internal auditors of the selected public sector offices were the sources of the data, collected via a questionnaire. The findings of this study show a direct relationship between internal audit effectiveness and such factors as management perception, management support, organisational independence of internal auditors, adequate and competent internal auditor’s staff, and the presence of an approved internal audit charter. According to the regression output, management support, the existence of adequate and competent IA staff, and the availability of an approved IA charter contributed to the internal audit effectiveness in the public sector significantly and positively. The public sector offices should understand that the contributions of these variables were collectively significant in identifying non- compliance activities in their offices and adding value to internal audit effectiveness. One of the major motive behind changes in internal control is surrounded with vast activities of gross corporate misconducts (Mahmood et al., 2020). This study details the importance of public sector audit activity to effective governance and seeks to define the key elements needed to maximize the value the public sector audit provides to all levels of the public sector (shezad , hamawandy, 2020). Corporate governance mechanisms are one of most important factors which have effects on the firm performance because the managers have their own interests which are sometimes different from shareholders' interests (Al-Kake & Hasan, 2019).